(untitled) (Eurasian Medical Research Periodical, 2022)
Cancer is without a doubt a major global issue, because it is the second most common reason of mortality universal. Due to greater exposure to danger factors and longer life expectancies, the prevalence of many malignancies has grown in both industrialized and developing nations. Among all cancers, the breast malignant tumor is one of the most prevalent.